Social Media Addiction and its Impact on Attitude towards Health-related Information during the Coronavirus Disease 2019 Pandemic – A Cross-sectional Survey - C. Govindaswamy; A. V. Suhas Bhargav; M. S. Narendra Kumar (Indian Journal of Psychiatric Nursing)
Background: The coronavirus disease 2019 (COVID-19) pandemic, marked by 45 million cases in India, highlights the imperative of effective information dissemination. This study explores the upswing in social media usage during the pandemic and its impact on public perspectives regarding COVID-19 information. Objectives: In the face of pandemic challenges, the study examines sociodemographic variables influencing social media engagement and assesses their association with attitudes and behaviors toward COVID-19. The primary focus is on comprehending addictive patterns of social media use and their correlation with demographic factors. Materials and Methods: Conducted at Mysore Medical College and Research Institute, a 6-month cross-sectional survey obtained data from 352 participants through a web-based platform. Statistical analyses, utilizing the Flu TElephone Survey Template and the Social Media Disorder Scale, explore connections between sociodemographic variables, COVID-19 information credibility, and addictive social media patterns. Results: The study discloses a notable addictive pattern in social media use (29.8%), with educational level, residence, and family income influencing addiction. Information credibility and trust in district administration are linked to addictive usage. Associations are identified between postinformation exposure attitudes, such as anxiety and dependence, with addictive patterns. Conclusion: This study highlights the escalating trend of social media addiction during the pandemic, emphasizing the necessity for targeted interventions. Sociodemographic elements, in conjunction with information credibility, offer crucial insights for crisis communication, guiding global health authorities and policymakers in promoting responsible social media use during crises.